Biofunctional Constituents from Liriodendron tulipifera with Antioxidants and Anti-Melanogenic Properties - Li, Wei-Jen (MDPI, 2013)
From the stems of Liriodendron tulipifera, seventeen known compounds have been extracted, isolated and purified. By using spectroscopic analysis, the structures of these pure constituents were determined as three lignans, four steroids and ten benzenoids. Identified compounds were screened for antioxidant abilities using: 1,1-diphenyl-2-picrylhydrazul (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) scavenging free radical activity assays; metal chelating power test; and ferric reducing/antioxidant power (FRAP) examination. The result revealed that seventeen compounds had potential anti-oxidative capabilities. In addition, the anti-tyrosinase effect was determined by calculating the hydroxylation of L-tyrosine to L-dopa and the oxidization of L-dopa to dopaquinone, according to in vitro mushroom tyrosinase evaluation platform. Furthermore, based on assays on B16F10 cell line, our data suggest that five compounds isolated from L. tulipifera would be able to inhibit tyrosinase activity and reduce the melanin content in animal cells. Therefore, some of the examined compounds could be potentially used in the cosmetic skin whitening business, therapeutic applications or the food industry.